Coronal Conditions for the Occurrence of Type II Radio Bursts - Kouloumvakos Athanasios; Rouillard Alexis; Warmuth Alexander; Magdalenic Jasmina; Jebaraj Immanuel C; Mann Gottfried; Vainio Rami; Monstein Christian (IOP PUBLISHING LTD, 2022)
Type II radio bursts are generally observed in association with flare-generated or coronal-mass-ejection-driven shock waves. The exact shock and coronal conditions necessary for the production of type II radio emission are still under debate. Shock waves are important for the acceleration of electrons necessary for the generation of the radio emission. Additionally, the shock geometry and closed field line topology, e.g., quasi-perpendicular shock regions or shocks interacting with streamers, play an important role for the production of the emission. In this study we perform a 3D reconstruction and modeling of a shock wave observed during the 2014 November 5 solar event. We determine the spatial and temporal evolution of the shock properties and examine the conditions responsible for the generation and evolution of type II radio emission. Our results suggest that the formation and evolution of a strong, supercritical, quasi-perpendicular shock wave interacting with a coronal streamer were responsible for producing type II radio emission. We find that the shock wave is subcritical before and supercritical after the start of the type II emission. The shock geometry is mostly quasi-perpendicular throughout the event. Our analysis shows that the radio emission is produced in regions where the supercritical shock develops with an oblique to quasi-perpendicular geometry.